YOUNG LECTURERS IN THE SYSTEM OF HIGHER EDUCATION OF RUSSIA: TRENDS AND PROSPECTS - Elena A. Berezovskaya (Moscow Polytechnic University, 2016)
The article discusses the negative trends in higher education recruitment. The author proposes a set of measures aimed at recruitment and retaining of young teachers at university taking into account the structure of their needs. The universities are not able or do not consider it necessary to meet adequately the current needs of young lecturers, which leads to «aging » of university teaching staff. The analysis of the situation and the proposed set of measures allows to make a conclusion about the strengthening of negative trends in attracting and retaining young teachers at university.